Gastrochilus yehii sp. nov. (Orchidaceae) from Taiwan - Lee, Chi Te; Wu, Jin Hua; Wang, Yu Qi; Hsieh, Szu I (Phytotaxa, 2023)
Gastrochilus yehii S. I. Hsieh, C. T. Lee & J. H. Wu, a new species of Orchidaceae discovered in Taiwan, is described and illustrated. It is morphologically close to G. ciliaris F. Maek., G. deltoglossus T.C. Hsu, S.I. Hsieh, J.H. Wu & H.C. Hung, and G. raraensis Fukuy. The distinguishing characters of G. yehii are semiorbicular epichile, which is whitish with purple dots and adaxial with densely long-hairy ciliate margin, and subconical hypochile, which is purple with reddish speckles.